2020
DOI: 10.3390/app10196922
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Supplementing Pig Diet with Chestnut Wood Extract or Hops on Fresh Meat and Dry-Cured Products

Abstract: Oxidation is one of the major reasons for impaired quality of meat and meat products but can be prevented by the addition of antioxidants. In the present study, the effect of dietary sweet chestnut wood extract and hop cones on the quality and oxidative stability of meat and dry-cured products was investigated. Control pigs (N = 11) were fed a commercial diet (13.1 MJ metabolizable energy, 15.5% crude protein), while the other two experimental groups were supplemented with 3% of sweet chestnut wood extract (Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Regarding the antioxidant abilities of chestnut wood extracts, Faraone et al [ 102 ] showed a high reducing ability of radical DPPH (1234 mg TE/g) and ferric reducing antioxidant power (2263 mg TE/g). Additionally, Tomažin et al [ 103 ] studied the oxidative stability of meat by adding chestnut wood extract to the diet of pigs. Among various indicators, the main effects observed were an increase in the water holding capacity and a positive color evolution of dry-cured bellies, due to the antioxidant supplementation.…”
Section: The Main Fruit Trees In Europe: Bioactive Compounds From Woo...mentioning
confidence: 99%
“…Regarding the antioxidant abilities of chestnut wood extracts, Faraone et al [ 102 ] showed a high reducing ability of radical DPPH (1234 mg TE/g) and ferric reducing antioxidant power (2263 mg TE/g). Additionally, Tomažin et al [ 103 ] studied the oxidative stability of meat by adding chestnut wood extract to the diet of pigs. Among various indicators, the main effects observed were an increase in the water holding capacity and a positive color evolution of dry-cured bellies, due to the antioxidant supplementation.…”
Section: The Main Fruit Trees In Europe: Bioactive Compounds From Woo...mentioning
confidence: 99%